Conversion of 2D line drawings to 3D models - Yong, Calwin Wearn Tsun. (2013)
This project aims to investigate the theoretical and practical limitations of a geometric reconstruction system which implements an algorithm based on the cubic corner method to convert 2D line drawings into 3D models. Given a cubic corner in a 2D line drawing, it is possible to determine the (x, y, z) coordinates for all endpoints connected to the corner, followed by the planes of faces connected to the corner and subsequently all vertices in the drawing. In theory, the cubic corner method can be used to reliably recover 3D objects from accurate 2D line drawings comprised of cubic graphs; however this is not true in the case of non-cubic graphs, as drawings containing vertices of degree four or higher may not always be recoverable. Some objects were only recoverable when starting from certain cubic corners or were completely unrecoverable.